Rapid detection of Clostridium perfringens in food by loop-mediated isothermal amplification combined with a lateral flow biosensor - Sridapan, Thanawat (PLoS One, 2021)
Clostridium perfringens is a key anaerobic pathogen causing food poisoning. Definitive detection by standard culture method is time-consuming and labor intensive. Current rapid commercial test kits are prohibitively expensive. It is thus necessary to develop rapid and cost-effective detection tool. Here, loop-mediated isothermal amplification (LAMP) in combination with a lateral-flow biosensor (LFB) was developed for visual inspection of C. perfringens-specific cpa gene. The specificity of the developed test was evaluated against 40 C. perfringens and 35 other bacterial strains, which showed no cross-reactivity, indicating 100% inclusivity and exclusivity. LAMP-LFB detection limit for artificially contaminated samples after enrichment for 16 h was 1–10 CFU/g sample, which was comparable to the commercial real-time PCR kit. The detection performance of LAMP-LFB was also compared to culture-based method using 95 food samples, which revealed the sensitivity (SE), specificity (SP) and Cohen's kappa coefficient (κ) of 88.0% (95% CI, 75.6%-95.4%), 95.5% (95% CI, 84.8%-99.4%) and 0.832 (95% CI, 0.721–0.943), respectively. Area under the receiver operating characteristic (ROC) curve was 0.918 (95% CI, 0.854–0.981), indicating LAMP-LFB as high relative accuracy test. In conclusion, LAMP-LFB assay is a low-cost qualitative method and easily available for routine detection of C. perfringens in food samples, which could serve as an alternative to commercial test kit.